SPATIO-TEMPORAL ANALYSIS OF SURFACE TEMPERATURE INDICATORS AS A WAY OF EVALUATING AREAS WITH FOREST PRESERVATION - Pereira dos Santos, Arthur; Henrique Simionatto, Henzo; Moreira Nery, Liliane; Collins da Cunha e Silva, Darllan (Revista Geográfica de América Central., 2025)
This article aims to analyze the variation of the Soil Surface Temperature (LST) and the Thermal Dryness Index (TVDI) in the hydrographic sub-basin that supplies the municipality of Paracatu, Brazil, and the Paracatu State Park, located in the interior of the basin and created to preserve the cerrado biome, restrict agricultural activities and guarantee water resources for local public supply. Images from the Landsat 5 and 8 satellites were used, whose results indicate that changes in land use are contributing to the water stress of the vegetation present there, and the spatial behavior of LST and TVDI indicates that the creation of the Park was an efficient practice in the preservation of the biome, concluding that they are timely indicators for the monitoring and management of public agencies to monitor human activities.